The influence of the national drug price negotiation policy reform on the medical expenses of patients in Xuzhou City: an interrupted time series analysis - Qin, Zhaohui; He, Meng; Shen, Huangying; Liu, Sha; Xu, Shuo; Chen, Lijiang (Frontiers in Public Health, 2024)
Background: To reduce the burden of patients' medical care, the Xuzhou Municipal Government has initiated an exploratory study on the supply model and categorised management of nationally negotiated drugs. This study aims to understand the extent to which Xuzhou's 2021 reform of the National Drug Price Negotiation (NDPN) policy has had a positive impact on the healthcare costs of individuals with different types of health insurance.The Interrupted Time Series Analysis method was adopted, and the changes in average medical expenses per patient, average medical insurance payment cost per patient and actual reimbursement ratio were investigated by using the data of singledrug payments in Xuzhou from October 2020 to October 2022.Results: Following the implementation of the policy, there was a significant decrease in the average medical expenses per patient of national drug negotiation in Xuzhou, with a reduction of 62.42 yuan per month (P < 0.001). Additionally, the average medical insurance payment cost per patient decreased by 44.13 yuan per month (P = 0.01). Furthermore, the average medical expenses per patient of urban and rural medical insurance participants decreased by 63.45 yuan (P < 0.001), and the average monthly medical insurance payment cost per patient decreased by 57.56 yuan (P < 0.04).However, the mean total medical expenditures for individuals enrolled in employee medical insurance decreased by 63.41 yuan per month (P < 0.001), whereas the monthly decrease was 22.11 yuan per month (P = 0.21). On the other hand, there was no discernible change in the actual reimbursement ratio.After the adoption of the NDPN policy, a noticeable decline has been observed in the average medical expenses per patient and the mean cost of the average medical insurance payment per patient, although to a limited extent. Notably, the reduction in employee medical insurance surpasses that of urban and rural medical insurance.